The Effect of the Number of Adjuvant Chemotherapy Cycles Following Cancer Surgery on Taste Alteration, Energy Intake, and Life Quality: 6-Month Follow-Up Study - Can Selim Yilmaz; Hilal Caliskan İzgi; Perim Fatma Türker (Life, 2025)
This study aimed to investigate the effect of the number of adjuvant chemotherapy cycles on taste alteration, energy intake, and life quality. This study was conducted with 87 adult patients with newly diagnosed early-stage cancer, treated by surgery and receiving adjuvant chemotherapy (two groups received <4 and ≥4 cycles). Taste alteration was assessed with the Chemotherapy-induced Taste Alteration Scale, and life quality with the Functional Assessment of Cancer Therapy. Patients who received ≥4 cycles showed significantly higher “Decline in Basic Taste”, “Phantogeusia and Parageusia”, and “General Taste Alterations” subscale scores at the end of treatment (d = 0.945, d = 1.200, d = 0.928, respectively; p < 0.001) and 3 months later (d = 0.515, d = 0.605, d = 0.985, respectively; p < 0.05). Quality of life scale total score and “physical well-being” and “functional well-being” subscale scores were significantly lower in patients received ≥4 cycle at the end of treatment (d = 0.590, d = 0.500, d = 0.621, respectively; p < 0.05) and 3 months later (d = 0.500, d = 0.516, d = 0.562, respectively; p < 0.05) but improved within 6 months. Significant correlations were found between taste alterations and recent weight loss, affordability of energy requirements, and decreased quality of life. A higher number of adjuvant chemotherapy cycles was associated with greater taste alterations, nutritional challenges and lower quality of life, especially in the early post-treatment. These changes are often transient and tend to return to baseline levels within 3–6 months after treatment.